1980
DOI: 10.1128/jb.143.2.772-780.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cellular location of enzymes involved in chondroitin sulfate breakdown by Bacteroides thetaiotaomicron

Abstract: Bacteroides thetaiotaomicron, a gram-negative anaerobe found in human colons, could utilize chondroitin sulfate, a tissue mucopolysaccharide, as its sole source of carbohydrate. The enzymes responsible for the breakdown of chondroitin sulfate by B. thetaiotaomicron were similar to those produced by Proteus vulgaris and Flavobacterium heparinum and included a lyase (EC 4.2.2.4), which degraded chondroitin sulfate into sulfated disaccharides, sulfatases (EC 3.1.6.4), which removed the sulfate residues, and a glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 26 publications
(20 reference statements)
1
68
0
Order By: Relevance
“…A recent study of enzymes involved in the breakdown of the mucopolysaccharide chondroitin sulfate by Bacteroides thetaiotaomicron has shown that the first degradative enzyme is in the periplasmic space (A. Salyers and O'Brien 1980). Solubility or hydration state of the xylan appears to be an important factor in enzymic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of enzymes involved in the breakdown of the mucopolysaccharide chondroitin sulfate by Bacteroides thetaiotaomicron has shown that the first degradative enzyme is in the periplasmic space (A. Salyers and O'Brien 1980). Solubility or hydration state of the xylan appears to be an important factor in enzymic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two arguments speak against this hypothesis. First, the B. thetaiotaomicron chondroitin sulfatases have been shown to be intracellular [181], and all the Ser-type sulfatases identi¢ed to date carry a signal sequence for export to the periplasm. Secondly, the changes in protein expression observed by 2D-PAGE in the chuR mutant are inconsistent with a role of ChuR solely as a modifying protein, though such an e¡ect could be caused by decreased stability of the target proteins if they remain unmodi¢ed (as has been observed for the C51A mutant of P. aeruginosa arylsulfatase [13]).…”
Section: Carbohydrate Sulfatasesmentioning
confidence: 99%
“…The fate of sulphate groups was not investigated in any of the studies cited above. Because desulphation of other sulphated substrates (mucin, chondroitin sulphate) has been shown to occur after depolymerization, through the activities of bacterial cytoplasmic enzymes (Salyers and O'Brien 1980;Wilkinson and Robertson 1988), fucans are likely to retain their sulphate groups during transit of the colon, thereby manifesting high cationic exchange capacities throughout the digestive tract. This would be of nutritional and physiological significance due to the occurrence of ionic exchange reactions, an example being the binding of bile salts.…”
Section: Fucansmentioning
confidence: 99%